2008
DOI: 10.1002/ajh.21250
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐associated plasmablastic lymphoma: Lessons learned from 112 published cases

Abstract: Plasmablastic lymphoma (PBL) is a distinct subtype of non-Hodgkin B-cell lymphoma, originally described with a strong predilection to the oral cavity of human immunodeficiency virus (HIV)-infected individuals. Data regarding patient age and gender, HIV status, initiation of and response to highly active antiretroviral therapy (HAART), tumor extent, pathology, treatment, and outcome were extracted from 112 cases of PBL identified in the literature. The median age at presentation was 38 years with a male predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
294
5
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(328 citation statements)
references
References 46 publications
(40 reference statements)
18
294
5
11
Order By: Relevance
“…The mean CD4 count in patients with PBL in our study is in-keeping with that quoted by Castillo et al 153 (<200/mm 3 ) and lower than the CD4 count of 300/mm 3 reported in a case study by Flaitz et al 153 154 Two cases of PBL occurred in the oral cavity and seven were diagnosed at extra-oral and extranodal topographic sites. While classic blast-like morphology was evident in the tumours occurring in the oral cavity, morphologic features of plasmacytic Overall, EBV LMP1 immunoexpression was detected in 3/9 PBL cases.…”
Section: Survival Functionssupporting
confidence: 92%
“…The mean CD4 count in patients with PBL in our study is in-keeping with that quoted by Castillo et al 153 (<200/mm 3 ) and lower than the CD4 count of 300/mm 3 reported in a case study by Flaitz et al 153 154 Two cases of PBL occurred in the oral cavity and seven were diagnosed at extra-oral and extranodal topographic sites. While classic blast-like morphology was evident in the tumours occurring in the oral cavity, morphologic features of plasmacytic Overall, EBV LMP1 immunoexpression was detected in 3/9 PBL cases.…”
Section: Survival Functionssupporting
confidence: 92%
“…However, in recent years, several cases of PBL have been reported at extraoral sites, including the skin, [2] subcutaneous tissue, [3] stomach, [4] anal mucosa or perianal area [5], lung [6] lymph node [7], and other regions. Small intestine has rarely been reported as a site for PBL with only five cases [8][9][10][11][12] reported in the literature before, present case being the sixth case.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the American Journal of Hematology, Castillo et al [3] present the first extensive literature review of the epidemiology, clinical findings, pathology, treatment, and outcome of 112 patients with HIV-associated PBL. The authors point out that HIV-associated PBL tends to affect young men with CD41 counts less than 200 cells/mm 3 .…”
mentioning
confidence: 99%
“…The authors point out that HIV-associated PBL tends to affect young men with CD41 counts less than 200 cells/mm 3 . The consistent presence of plasma cell markers and frequent absence of B-cell markers are key pathologic features of this entity [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation